A comparative study on the time to achieve negative nucleic acid testing and hospital stays between danoprevir and lopinavir/ritonavir in the treatment of patients with COVID‐19. Issue 11 (24th June 2020) - Zhang, Zhicheng; Wang, Shumei; Tu, Xianglin; Peng, Xuping; Huang, Yanxia; Wang, Li; Ju, Weihua; Rao, Jianfeng; Li, Xue; Zhu, Donghong; Sun, Huabao; Chen, Hongyi
Abstract: In late December 2019, coronavirus disease 2019 (COVID‐19) first broke out in Wuhan, China, and has now become a global pandemic. However, there is no specific antiviral treatment for COVID‐19. This study enrolled 33 COVID‐19 patients in the nineth hospital of Nanchang from 27th January to 24th February 2020. Clinical indexes of patients upon admission/discharge were examined. Patients were divided into two groups according to different treatment plans (danoprevir and lopinavir/ritonavir). The days to achieve negative nucleic acid testing and the days of hospital stays were counted and statistically analyzed. COVID‐19 patients treated with danoprevir or lopinavir/ritonavir were all improved and discharged. Indexes like blood routine, inflammation and immune‐related indexes were significantly recovered after treatment. Additionally, under the circumstance that there was no significant difference in patients' general information between the two groups, we found that the mean time to achieve both negative nucleic acid testing and hospital stays of patients treated with danoprevir were significantly shorter than those of patients with lopinavir/ritonavir. Collectively, applying danoprevir is a good treatment plan for COVID‐19 patients. Highlight: 1. The average time to achieve negative nucleic acid testing of COVID‐19 patients treated with danoprevir was obviously shorter than that of patients treated with lopinavir/ritonavir. 2. The average time of hospital stays of COVID‐19 patients treated with danoprevir was significantly shorter than that of patients treated with lopinavir/ritonavir.